2012
DOI: 10.1021/ef300330b
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on the Separation of Air-Mixed Coal Bed Methane in THF Solution by Hydrate Formation

Abstract: Because of the technology limitation and safety requirement, a large amount of air-mixed coal bed methane is released directly to the atmosphere. It leads to severe waste of resources and exacerbates the greenhouse effect. This work tries to alleviate this problem by separating CH 4 from a mixture of CH 4 and N 2 via hydrate separation method. Several experiments were systematically carried out in 6 mol % tetrahydrofuran (THF) solution to separate CH 4 /N 2 gas mixtures containing 4.90 to 71.23 mol % CH 4 . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…4 and 5 show the pressure effect on the separation results with 37.5 mol% CH 4 /N 2 under constant temperature, feed gas flow (240 L/h), liquid flow (40 L/h), and TBAB solution (10 wt%). We can find that the concentration of CH 4 in both unhydrated gas and dissociated gas decreases with the pressure, which is in good agreement with the results of the equilibrium separation of CH 4 /N 2 via hydrates formation [9].…”
Section: Continuous Separation Of Ch 4 /N 2 Via Hydrates Formation Insupporting
confidence: 88%
See 1 more Smart Citation
“…4 and 5 show the pressure effect on the separation results with 37.5 mol% CH 4 /N 2 under constant temperature, feed gas flow (240 L/h), liquid flow (40 L/h), and TBAB solution (10 wt%). We can find that the concentration of CH 4 in both unhydrated gas and dissociated gas decreases with the pressure, which is in good agreement with the results of the equilibrium separation of CH 4 /N 2 via hydrates formation [9].…”
Section: Continuous Separation Of Ch 4 /N 2 Via Hydrates Formation Insupporting
confidence: 88%
“…With the advantages of simple process, mild operation conditions, low cost and energy consumption, hydrate separation method is widely applied to remove CO 2 , and recover H 2 and hydrocarbons, etc. [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…According to studies on pure water, promoters, such as tetrahydrofuran (THF), cyclopentane, propane and isobutene, reduce the hydrate-formation pressure (Sabil et al 2010). Sun et al (2012) found that THF significantly reduced the gas hydrate-formation pressure in the separation of N 2 and CH 4 . This method can also be applied for reducing the hydrate-formation pressure in porous media.…”
Section: Introductionmentioning
confidence: 97%
“…Besides, the stored methane can be released immediately when pressure is reduced and the amount of methane released increases with time at almost a constant rate. The porous media with a pore size of 2-6 nm was shown to be more suitable for the hydrate formation (Zhou et al 2005b(Zhou et al , 2010Liu et al 2006a;Sun et al 2007;Liu et al 2011;Wei et al 2014). Porous media with high surface areas provide improved access for both the water and the gases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this method is also ideal to recover CH 4 from air-mixed CBM because the presence of water could effectively reduce the possible explosion between CH 4 and air. [23] In this study, we investigated the separation of a CH 4 /N 2 mixture by hydrate formation of THF solution and dissociation to develop a viable pathway for future industrial application.…”
Section: Introductionmentioning
confidence: 99%